Dialektics of Bicultural Identity in Intercultural Communication: A Phenomenological Study Approach - Halimatusa’diah HALIMATUSA'DIAH (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to understand and analyze the ways in which bicultural individuals identify as Betawi people in building meaning about their identity in situations of intercultural communication. This study uses a qualitative approach that in its implementation uses a type of understanding. The subjects of the study were bicultural individuals in Jakarta who identified themselves as Betawi people. This study concludes that, first, the meaning of identity to be a Betawi Person is implemented by bicultural individuals by internalizing Betawi cultural values in their daily lives. Local wisdom "openness and equality", "living beneficially for others" and avoiding primordialism are values that are widely applied by bicultural individuals in all situations. Second, in the situation of intercultural communication, Betawi becomes the main identity used by informants. Meanwhile, occupational identity becomes the main identity in the context of intracultural meetings (ingroups). Third, this study also found differences in the ethos of figures caused by differences in age and types of daily activities carried out by the study subjects. This study recommends further research to explore the experiences of other subgroups such as the Betawi millennial generation.